Poorly known relatives of Arabidopsis thaliana - Clauss, Maria J.; Koch, Marcus (Trends in plant science, 2006)
Non-model Arabidopsis species have been widely used as outgroup taxa in studies of molecular evolution. In Arabidopsis lyrata, Arabidopsis halleri and Arabidopsis arenosa, traits pertaining to self-incompatibility, heavy metal tolerance and inter-specific hybridization have been subjected to detailed genetic analysis. However, the full potential for exploring the causes and consequences of natural variation in complex traits within the genus Arabidopsis has not been widely appreciated or realized. Here, we draw on broadly dispersed information to characterize the basic biology, ecology, population genetics and molecular evolution for these three non-model Arabidopsis species. We illustrate how the wealth of functional and genomic tools pioneered in A. thaliana can be applied to gain insights into adaptive evolution of ecologically important traits and genome-wide processes, such as polyploidy, speciation and reticulate evolution, within and among Arabidopsis species.
Gesehen am 27.01.2017